2012
DOI: 10.1603/ec11433
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Preference and Movement of <I>Nezara viridula</I> and <I>Euschistus servus</I> (Hemiptera: Pentatomidae) on Individual Cotton Plants

Abstract: Experiments were conducted in an environmental growth chamber to determine the movement and feeding preferences of Nezara viridula (L.) and Euschistus serous (Say) on individual cotton plants. Fifth instars were caged by species on a single cotton plant (FM 9063 B2F) containing four discrete boll sizes ranging from 1.1 to 3.0 cm in diameter over a period of 5 d per replication. Two digital video cameras were simultaneously focused on each of the four bolls per plant to visually confirm stink bug resting and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Pentatomids exhibit differing preferences for oviposition sites. For example, E. servus oviposits more commonly on smaller cotton bolls, whereas N. viridula prefers larger bolls (Huang and Toews 2012). In general, H. halys is considered an arboreal species (Rice et al 2014), although it also feeds and oviposits on a range of plants and shrubs (www.stopbmsb.org) and typically deposits it eggs on the underside of host plant leaves (Nielsen and Hamilton 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pentatomids exhibit differing preferences for oviposition sites. For example, E. servus oviposits more commonly on smaller cotton bolls, whereas N. viridula prefers larger bolls (Huang and Toews 2012). In general, H. halys is considered an arboreal species (Rice et al 2014), although it also feeds and oviposits on a range of plants and shrubs (www.stopbmsb.org) and typically deposits it eggs on the underside of host plant leaves (Nielsen and Hamilton 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is similar to the results from a pitfall trap study, which reported that phytophagous hemipterans were strongly diurnal, with activity concentrated from 1100 to 1600 hours (Dondale et al 1972). In addition, Huang and Toews (2012) reported two pentatomids, the brown stink bug, Euschistus servus (Say), and the southern green stink bug, Nezera viridula (L.), moved more frequently among cotton bolls during photophase than scotophase. In contrast, Krupke et al (2006) reported a nocturnal attribute of Euschistus conspersus (Uhler) that the mating behavior was peaked at 2300 hours in a pheromone bait study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies did not investigate the inßu-ence of environmental variables on B. hilaris diel activity or feeding behavior. Diel activity patterns on ßight or feeding have been studied for other related pentatomids (Shearer and Jones 1996, Krupke et al 2006, Huang and Toews 2012. A clear understanding of factors that inßuence population abundance and associated feeding injury on host crops is essential for the development of a sustainable management approach for this new pest (Kogan 1988).…”
mentioning
confidence: 99%
“…Direct sunlight and time of day may also inßuence sampling stink bugs with a sweep net. Stink bugs move on individual cotton plants during daytime in search of food (Huang and Toews 2012). Similarly, intercrop movement of stink bugs occur between cotton and other Þelds crops (Tillman et al 2009, Toews andShurley 2009) based on the maturity of the crops.…”
Section: Discussionmentioning
confidence: 99%